Spatiotemporal variation of household water consumption and coping strategies in water-stressed city of arid and semiarid Northwest China - Dang, Xiaohu; Li, Lin; Fan, Liangxin (Frontiers in Environmental Science, 2022)
Increasing water demand due to population growth and urbanization causes cities in arid and semiarid regions in China to face increasing water scarcity. Understanding the spatiotemporal patterns of water consumption and its driving factors is of considerable importance in formulating public policy and alleviating the urban water crisis. In this study, spatiotemporal variations of water consumption in 42 cities in Northwest China were identified, and their influencing factors were determined by cluster tree and factor analyses. Results indicate that per capita household water consumption decreased by 9.5% from 2003 to 2020, with significant spatiotemporal variations decreasing in cities with medium consumption (86.87–193.66 L/d per capita per day) but increasing in cities with low (<86.87 L/d per capita per day) and high consumption (>193.66 L/d per capita per day). The influencing factors vary across the three types of cities. An increase in the capacity of water supply and popularization of washing machines are the main reasons for the rise in water consumption for low and high-consumption cities, whereas the implementation of water-saving activities and improvements of reuse rate are the main reasons for reduction of water consumption for medium-consumption cities. Findings suggest that improving water-saving appliances and water-use efficiency in cities with high-water consumption and increasing water supply capacity in cities with low-water consumption requires consideration in urban sustainable water management strategies in Northwest China.